Building Information Modeling Concept And Its Application in Building Renovation Stage In Term Of Time Efficiency - Machdi, Ardhiana Muhsin (Universitas Pendidikan Indonesia, 2019)
Abstract—Nowadays Building Information Modeling, known as BIM has become a common topic in construction technology. Indonesian government has even accelerated the implementation of BIM as a requirement in planning above 2000 m2 since year 2018. The word renovation in BIM life cycle means one of the post-project building phases after maintenance, rehabilitation but before reach demolition phases as an ending of the building. On the other hand, renovation is not a strange thing for the Indonesian people and has direct meaning to its activity. Even though occupying a new property, there is always a tendency to change, add or even reduce some parts of existing buildings. Renovation is also unavoidable when there is a change in function in a building and it can be classified as adaptive reuse as part of the concept of sustainable building, a preservation and rehabilitation of an old building that has unique design or contains certain historical significance. This research is structured and focuses more on the issue of time efficiency which is very significant in the renovation stage. The method used in the form of a comparison between conventional methods with methods that apply the BIM concept. This is interesting to be observed as the benefits of research so that the concept of BIM can be understood and seen its real advantages.Keywords—building information modeling, renovation, efficiency